Effect of the application of seminal plasma on the pregnancy rate in alpacas with different copula times - Sánchez P., Renato (2019)
The aim if this study was to determine the effect of copulation time and the intramuscular application of seminal plasma (PS) in alpacas on pregnancy rate. A total of 161 female alpacas with ≥15 days postpartum, with calf at foot, and with the presence of preovulatory follicle ≥7 mm, identified by ultrasonography were used. The animals were randomized into six groups: G1 (n = 28) 5 min of copula without PS application; G2 (n = 28) 5 min of copula with application of 1 ml of PS i.m.; G3 (n = 27) 10 min of copula without application of PS; G4 (n = 27) 10 min of copula plus 1 ml of PS; G5 (n = 26) >15 min of copula without PS; G6 (n = 25) >15 min of copula with 1 ml PS. To avoid the male effect, the same animal was used to mate a female from the PS group and another from the control group for each study time. Pregnancy diagnosis was done by transrectal ultrasonography 25 days after mating, obtaining 50.0, 64.3, 63.0, 70.4, 76.9 and 80.0% of pregnancy for G1, G2, G3, G4, G5 and G6 respectively. The results indicate a better pregnancy rate (p<0.05) of G6 with respect to G1, G2, G3 and G4, but similar to G5. The copulation time ≥15 minutes allowed a better pregnancy rate (p<0.05) compared to times of 5 and 10 minutes. The application of seminal plasma did not significantly improve the pregnancy rate 25 days post-copula.